Acute and long‐term management of food allergy: systematic review. Issue 2 (12th November 2013) - de, D.; Geromi, M.; Panesar, S. S.; Muraro, A.; Werfel, T.; Hoffmann‐Sommergruber, K.; Roberts, G.; Cardona, V.; Dubois, A. E. J.; Halken, S.; Host, A.; Poulsen, L. K.; et al.
Abstract Background Allergic reactions to food can have serious consequences. This systematic review summarizes evidence about the immediate management of reactions and longer‐term approaches to minimize adverse impacts. Methods Seven bibliographic databases were searched from their inception to September 30, 2012, for systematic reviews, randomized controlled trials, quasi‐randomized controlled trials, controlled clinical trials, controlled before‐and‐after and interrupted time series studies. Experts were consulted for additional studies. There was no language or geographic restrictions. Two reviewers critically appraised the studies using the appropriate tools. Data were not suitable for meta‐analysis due to heterogeneity so were narratively synthesized. Results Eighty‐four studies were included, but two‐thirds were at high risk of potential bias. There was little evidence about acute management for non‐life‐threatening reactions. H1‐antihistamines may be of benefit, but this evidence was in part derived from studies on those with cross‐reactive birch pollen allergy. Regarding long‐term management, avoiding the allergenic food or substituting an alternative was commonly recommended, but apart from for infants with cow's milk allergy, there was little high‐quality research on this management approach. To reduce symptoms in children with cow's milk allergy, there was evidence to recommend alternatives such as extensively hydrolyzed formula. Supplements such as probiotics have not proved helpful, but allergen‐specific immunotherapy may be disease modifying and therefore warrants further exploration. Conclusions Food allergy can be debilitating and affects a significant number of people. However, the evidence base about acute and longer‐term management is weak and needs to be strengthened as a matter of priority.